ChemInform Abstract: An Approach to Benzophosphole Oxides Through Silver‐ or Manganese‐Mediated Dehydrogenative Annulation Involving C—C and C—P Bond Formation. Issue 19 (13th May 2014) - Unoh, Yuto; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
Abstract It is demonstrated that Ag‐mediated dehydrogenative coupling of arylphosphine oxides with internal alkynes produces benzophosphole oxides in good yields.